Financial Management of Klungkung Regency in 2024 in Achieving an Unqualified Audit Opinion Amid Fiscal Dependency - Rafiqa Aurellia; Nurul Ambiah; Gelis Nurlisya (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2025)
This study aims to analyze the financial performance of the Klungkung Regency Government in 2024 based on the Regional Government Financial Statements (LKPD) audited by the Audit Board of Indonesia (BPK). The analysis focuses on identifying the fiscal condition, general financial management issues, and potential opportunities to improve regional financial independence. The research uses a qualitative descriptive approach through document analysis of financial statements, including the Budget Realization Report, Operational Report, Balance Sheet, Cash Flow Statement, Statement of Changes in Equity, and Notes to Financial Statements. The results indicate that the regional financial condition is relatively stable, supported by strong revenue performance, particularly from the tourism sector. However, several issues remain, such as low capital expenditure absorption, significant asset corrections, and weaknesses in internal control systems. These findings suggest that despite achieving an unqualified opinion, the local government still needs to improve financial management practices to enhance effectiveness, transparency, and accountability.